RESPONSE OF RED CABBAGE TO THE ADDING WHEAT PEATAND SPRAYING WITH ITS EXTRACT AND ORGANIC NUTRIENT VEGEAMINO ON QUALITATIVE CHARACTERISTICS OF HEADS - & AL-Ubaidy, AL-Zaidy (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
A field experiment was carried out at the Horticulture Dept. Fild– Coll. Agric,University of Baghdad , to study the response of red cabbage to the adding wheat peat and spraying its extract and organic nutrient vegeamino on qualitative characteristics of heads , using Raissa hybrid , during winter season of 2015-2016 . Afactorial experiment using Randomized Complete Block Design(RCBD) with threere plicaes were canducted , The First fatcor includes five levels of fertilizers , wethout-fertilizer (P0) , recommended chemical fertilizer ( 100 N ,120P205and120K2O kg . h -1( (P1) , organic fertilizer 7.5 tan.h-1(P2) , organic fertilizer 15 tan.h-1(P3) and organic fertilizer 30 tan.h-1(P4), The second factor includes four treatments , spraying only weter (E0) , extracts wheat peat (E1) at a concentration 2 ml.L-1 , organic nutrient vegeamino (E2) at 1 ml.L-1 and Interaction E1 + E2 (E3) , The results showed superiority of organic fertilizer treatment P4 in Vitamin C content (76.0mg .100 gm-1 ) , Folic acid (123.14µg.100gm-1 ) , percentage oftotai carbohydrates (4.593 % ) , protein (18.823 % ) , fiber (9.130% ) and lowest content of nitrate in the head (0.390 mg.gm-1 ) , E3 treatment showed a significant increase in the characteristicsaboveand gave greatest value reached 71.50mg . 100gm-1, 119.54µg.100gm–1 , 4.257 % , 17.702 % , 9.190 %andlowest content of nitrate inE0treatment (0.449 mg.gm–1), Interaction treatment of P4E3 gave the greatest value reached82.34mg.100gm1-, 145.79µg.100gm1-, 4.983 % , 20.516% , 11.790 %andlowest content of nitrate was inP0E0 treatment (0.332mg.gm–1 ).